Ronin - Frankenheimer, John 1930-2002; De Niro, Robert; Mancuso, Frank; Reno, Jean 1948-; McElhone, Natascha 1971-; Skarsga& 778;rd, Stellan; Bean, Sean; Pryce, Jonathan (United Artists Pictures, an FGM Entertainment Production, 1998)
A woman hires a team of masterless samurais known as Ronins to reclaim a mysterious suitcase. Conflicts arise when one Ronin betrays the team by swapping suitcases intending to fulfill his personal gains.